Oceanography and Creative Writing in Ernest Hemingway’s The Old Man and the Sea (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
The ability to psychologically reflect on past and present experiences, subject the mind to critical thinking and express oneself for entertainment, education, purgatory and other purposes is crucial in creative writing. Observations, personal feelings and thoughts could be communicated through literary writings such as poetry, prose and drama. This study, therefore, examines oceanography and creative writing in Ernest Hemingway’s The Old Man and the Sea. It focuses on the heroic battle of a solitary fisherman with a giant Marlin and nature in the oceanic ecosystems. The study adopts Sigmund Freud’s Psychoanalytic theory which focuses on the underlying factors that can spark up a writer’s imagination and creativity. The research is library based since the materials are not gathered through fieldwork but from critical and primary texts. The primary text chosen for this study was purposively selected by the researchers based on its thematic relevance to the objectives and subjected to qualitative (literary) analysis. Findings reveal the struggle of the protagonist against the Marlin and sharks, waves, current, climatic condition, and other elements in the oceanic ecosystems. Despite of the battle that lasted for three days in the marine world, Santiago is able to emerge victorious, arriving home with a giant Marlin of about eighteen feet tall. Ernest Hemingway has creatively expressed his observations in the ocean through fiction, thereby interfacing the inter-disciplines of oceanography and literature (literary writing). The study concludes that personal experiences and observations in the physical world can spark imagination and creativity as evident in Hemingway’s novella.
Keywords: Oceanography; creativity; literature; fiction; fishery